A Theoretical Model to Measure Managerial and Leadership Competence of Business School Managers - Shaikh, A.; Bisschoff, C. A.; Botha, C. J. (Journal of Economics and Behavioral Studies, 2018)
A theoretical model to measure managerial competence was developed by evaluating two previous models with similar aims. In addition to the original eight management competencies, another eight competencies were identified and applied to determine the management competencies needed in the Fourth Industrial Revolution with its fast-changing business environment. The article narrows down eleven management competencies and develops measuring criteria for each; in total 42 criteria. The eleven business competencies are leading change, cultural intelligence, team building, conflict management, communication skills, a global leader mindset, emotional intelligence, career awareness, personal value system, and external and ethical influences. The model is a theoretical model and presents management competencies relevant to the modern business environment. The value of this study resides in a strong theoretical basis for postmodern business environmental skills that managers need to maintain completeness of their organizations as well as providing a sound point of departure for other researchers of managerial competence.